Dichromated Gelatin in Optics - Sergio Calixto; Mariana Alfaro-Gomez (Gels)
Dichromated Gelatin (DCG) was first used in optics in 1872 by Lord Rayleigh. Then, in 1968, Shankoff suggested its use as a photosensitive material to record interference diffraction gratings and holograms. Diffraction efficiencies of nearly 100% were achieved. This review discusses some physical and chemical characteristics of DCG films; the fabrication methods of DCG films; and some of the applications of DCG films in holography, holography in real time, solar concentrators, optical elements, and relative humidity sensors.